Effects of liquid oils on partial coalescence and whipping capabilities of aerated emulsions: Differences between diacylglycerol and triacylglycerol - Xie, Pengkai; Xie, Rui; Lai, Junqi; Zou, Shuo; Lee, Yee Ying; Tan, Chin Ping; Zhang, Yufei; Wang, Yong; Zhang, Zhen (Elsevier, 2025)
Liquid oils are typically used to dilute solid fat in aerated emulsions, yet the structure of lipid components determines their functional properties. This study investigates the mechanism of liquid diacylglycerol (DAG) and triacylglycerol (TAG) on the whipping capabilities of aerated emulsions from the perspective of fat crystal- membrane interactions. Although there were no significant differences in thermodynamic properties, DAG significantly delayed the reduction in lamella thickness of fat crystals compared to TAG, thereby maintaining the density of the fat crystal network at high liquid oil levels. Additionally, the extra hydroxyl group in DAG, compared to TAG, enabled DAG-rich fat globules to occupy the air-liquid interface more rapidly, thereby significantly enhancing the occurrence and development of partial coalescence during whipping. Therefore, the whipping capabilities of aerated emulsions rich in DAG were greatly improved. This study enhances understanding of structural lipids in aerated emulsions and offers new insights into improving whipping capabilities.